Motivation use of urban green space in Taman Tasik Komanwel Bukit Jalil - Mohd Faiz, Mohamad Faizal (2019)
The poor maintenance of Taman Tasik Komanwel Bukit Jalil has been an issue to the users of the park. Despite the poor condition of facilities in the park, it still receives visitors. The objectives of this study are to identify the motivation of visitors to visit the park and investigate the types of facilities needed in Taman Tasik Komanwel Bukit Jalil. The data is obtained using a questionnaire and the results were analyzed using SPSS. Descriptive analysis, t-test, ANOVA, and crosstab analysis were used in this study. The findings showed that visitors’ main motivation to visit the park is to get fresh air. This is followed by the motivation to experience the calm and peaceful surroundings and to get away from daily pressure. Apart from that, the facilities that are most preferred by the visitors were the toilets, followed by exercise trails and dustbin. The findings of the study provides information on the motivation and important facilities to the authorities for improvement. This is important to enhance the use of recreational park among visitors, apart from managing the park facilities wisely.